Identifikasi Morfologi Trichopsis vittata dari Tiga Populasi Berbeda untuk Mendukung Sumber Belajar Mata Kuliah Ekologi Hewan - Rizky Putri Lestari; Khairul Khairul; Ilham Hakiki Harahap (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to analyze the morphometric and meristic characteristics of T. vittata from three populations as learning resources for the Animal Ecology course. This is a quantitative descriptive study using data collection methods involving purposive sampling from three research locations. Data analysis was performed using software through the Kruskal–Wallis test and Principal Component Analysis (PCA). The results showed that there were no significant differences in morphometric characteristics between populations. However, the PCA analysis showed a separation in two meristic characteristics, namely DR and CR, indicating physiological adaptation to habitat conditions. It was concluded that the morphological characteristics of T. vitatta related to environmental differences could be used as learning material for the Animal Ecology course. Keywords: Animal Ecology, Morphological Characteristics, Taxonomy, Trichopsis vittata